Model Pendidikan Karakter Bagi Anak Berkebutuhan Khusus - Rachmandhani, Muh. Shulthon; Sari, Novita; Lestari, Masita Ayu; Khoiriyah, Mar'atus Kusnul (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Character Education for Children with Special Needs (ABK) plays an important role in helping them reach the door to success. The right character education process is believed to help them become independent individuals and socialize with the surrounding environment. So that the character education process carried out by the Ponorogo Integrated Aisiyah Orphanage is interesting to study. This study aims to find a model of character education applied by the Panti Asuhan Aisiyah Tunanetra Terpadu Ponorogo, using a qualitative research method of the case study. The results showed that the character education model applied by the orphanage was a model of habituation and tadzkirah based on humanist independence.